A new strategy for describing the characteristics of bending line in flexible push bending. Issue 5 (30th July 2019) - Zhang, Zengkun; Wu, Jianjun; Shang, Qi; Jiang, Qiang; Yang, Junzhou; Guo, Ruichao
Abstract : Purpose: When manufacturing an arc-shaped tube product using push bending process, the transition zone and outfeed zone will inevitably occur. Transition zone and outfeed zone are caused by the kinematical motion of mobile tools. The existence of transition zone and outfeed zone will lead to a big deviation between the forming product and desired shape. To improve the forming quality of arc-shaped products in push bending, the transition zone and outfeed zone are investigated in this paper. Design/methodology/approach: A piecewise function is used to describe the bending characteristics along bending line, in which a series of vibration parameters are extracted and considered as control values. Findings: The new strategy is helpful for finding the relationship between tools motion and curvature distribution and improving the bending lines design procedure in flexible push bending. Originality/value: The new strategy is helpful for finding the relationship between tools motion and curvature distribution and improving the bending lines design procedure in flexible push bending.